2018
DOI: 10.1116/1.5029827
|View full text |Cite
|
Sign up to set email alerts
|

Real-space pseudopotential calculations for simulating noncontact atomic force microscopy images

Abstract: Noncontact atomic force microscopy (nc-AFM) with a CO-functionalized tip yields high resolution images under many situations. However, nc-AFM images are sometimes difficult to interpret when visualizing polycyclic aromatic hydrocarbons. The authors employ real-space pseudopotentials constructed using density functional theory to simulate nc-AFM images of benzene and dibenzo(cd,n)naphtho(3,2,1,8-pqra)perylene molecules with selected probe tips (such as CO, H2, N2, Br, and CH2O). The selected tips provide accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…FDET calculations for the tip were performed following a full DFT run of the sample system and using the Hartree potential, nuclear potential, and the charge density of the sample system as input. Our previous studies have shown the assumption that the tip does not have a significant effect on the structural and electronic properties of the sample is valid for the systems examined here. ,, …”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…FDET calculations for the tip were performed following a full DFT run of the sample system and using the Hartree potential, nuclear potential, and the charge density of the sample system as input. Our previous studies have shown the assumption that the tip does not have a significant effect on the structural and electronic properties of the sample is valid for the systems examined here. ,, …”
Section: Methodsmentioning
confidence: 64%
“…We generate 2D uniform grids over the sample molecule at three different tip heights and compute the total energy of the tip–sample system ( E ts ) at each grid point. In previous work, we verified that the tip–sample force gradient can be taken to be constant within an oscillation cycle. The relative frequency shift (Δ f ) can be computed from total energy calculations using a three-point central finite difference method , where E –1 , E 0 , and E 1 correspond to the total energy of the tip–sample system at three different heights for each grid point, and h is the separation distance between the planes.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…The challenge now is to distinguish the N atom. We observe contrast inversion [28][29][30] between C sites and hollow or heteroatom sites. Inversion usually hampers image interpretation; however, here it can be used to identify N from C. We employ a metallic tip composed of a Cu dimer.…”
Section: Resultsmentioning
confidence: 81%